Filsafat Pancasila dan Transformasi Pendidikan Virtual: Menjaga Humanisme di Tengah Digitalisasi: Pancasila Philosophy and Virtual Education Transformation: Maintaining Humanism in the Midst of Digitalization - Sabrina Cahaya Kirana; Cahaya Maulidina; Nurus Shaffiyatul Jannah; Ainur Rohmah; Naila Najwa (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The rapid advancement of digital technology has accelerated the transformation of education into more flexible and massive virtual models. However, this shift also presents serious challenges related to the erosion of humanistic values caused by technocratic approaches. In Indonesia, Pancasila as the state ideology and philosophical foundation offers an ethical and humanistic framework that can guide educational practices to remain learner-centered and human-oriented. This study aims to examine how the values of Pancasila, particularly humanism, can be integrated into the design and implementation of virtual education, as well as to identify the challenges and opportunities emerging in the process. A mixed-methods approach was employed, combining quasi-experimental design in online classes with qualitative analysis through interviews, focus group discussions, and document analysis. The findings indicate that integrating Pancasila-humanism values into virtual learning modules significantly enhances empathy, ethical awareness, and the quality of student interactions without reducing academic performance. Major challenges include limited lecturer competence in embedding philosophical values, student resistance, and infrastructural constraints. In conclusion, Pancasila remains relevant and applicable as a moral foundation to ensure that the digital transformation of education does not merely emphasize efficiency but also safeguards humanistic dimensions. The study recommends lecturer training, digital education policies based on Pancasila values, and further research on humanistic learning models in the digital era.